UJI EFEKTIVITAS SALEP EKSTRAK ETANOL RIMPANG JERINGAU (Acorus calamus L.) TERHADAP PENYEMBUHAN LUKA SAYAT - Linta Meliala (Jurnal Penelitian Farmasi & Herbal, 2020)
Introduction: Jeringau rhizome plants are one of the traditional plants which are used as antibacterial. Method: The extraction process was carried out by maceration using 80% ethanol. The effectiveness of jeringau rhizome testing was divided into 5 treatments, the positive group used betadine ointment, negative control using an ointment base, and the test group used ethanol extract ointment with 5%, 10% and 15% concentration. Cut wounds given to the rabbit's back with a 2 cm long wound and 2 mm deep, the ointment applied twice a day for 13 days and measured using a ruler or calipers. Result: The results show that Jeringau rhizome contains flavonoid, tannin, saponin, and alkaloid metabolites which can be used as wound heal wound healers. This study aims to determine its effectiveness as a wound healer wound. Conclusions: indicate that the ointment extract jeringau rhizome at a concentration of 15% is the most effective control as a wound healer but the ointment extract of jeringau rhizome ethanol extract is less effective when compared to betadine ointment as a wound healer in rabbits. .